Phytochemical screening and biological activities of Garcinia kola (bark, leaves and seeds) collected in Benin - ADOUKONOU-SAGBADJA, Hubert (My University, 2015)
Garcinia kola is a tropical plant which grows in moist forest. It seeds are edible and are consumed for their multiple property. This study aimed at making phytochemical screening and evaluating some biological activities of G. kola organs (bark, leaves and seeds) extracts. The selected organs powdered were used for phytochemical screening and extractions. The antibacterial activity was tested on 10 references strains and 28 meat isolated Staphylococcus strains by agar perforation method. The antifungal activity of three fungal strains was determined on the potato-dextrose agar medium mixed with the tested extract. The antioxidant activity was determined by both DPPH and ABTS methods. The results reveal that 40% of studied secondary metabolites were present in the seeds against 28.57% in the leaves as the bark. The reference and meat isolated strains inhibitory diameter ranged from 28 ± 2.3 mm (S. haemolyticcus) to 7.5 ± 0.70 mm (E. coli). All extracts had a minimum inhibitory concentration (MIC) lower than 20 mg/ml, while the minimum bactericidal concentration (MBC) was ≥ 20 mg/ml for some tested extracts. The lowest MIC and MBC was 0.039 mg/ml with C. albicans. The fungal strains susceptibility varied (p  0.001) depending on extracts. The seeds ethyl acetate extract displays the better antioxidant activity with DPPH (25.03 ± 3.64 μg/μl) and ABTS (22.99 ± 1.34 μmol EqAA/g) methods. The LD50 of the extracts was greater than 0.1 mg/ml and not exhibiting toxicity. The leaves extract had the best bactericidal effects while the seeds extract presented better antifungal and antioxidant activity.
Keywords: Antifungal; Staphylococcus; food strains; antioxidant; cytotoxicity; Benin.